Economic Implications of Wives' Fulfillment of Family Support: A Review from the Perspectives of Syafi'i and Hambali - Mhd. Mahya Nasuha; Dhiauddin Tanjung; Ramadhan Syahmedi Siregar (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the economic implications of wives’ fulfillment of family support, analyzed through the perspectives of the Syafi'i and Hambali Islamic legal schools. The purpose is to understand how these jurisprudential views influence family economic dynamics and the role of wives in sustaining family welfare. The study employs a qualitative literature review methodology, analyzing classical and contemporary fiqh texts and scholarly interpretations related to women’s financial contributions within the household. The findings indicate that both the Syafi'i and Hambali schools provide nuanced frameworks recognizing wives’ involvement in family economic matters while emphasizing responsibilities aligned with social and religious norms. This review highlights the importance of integrating religious jurisprudence with socio-economic realities to foster family sustainability.